Landasan Syariah dalam Etika Periklanan - Hanif, Hasnan (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2018)
The conventional ethics concept has difference color with Islamic ethics on implementation in daily lives. The ethics in Islamic teaching follows the rule of valid and invalid (halal and haram) including the way of reaching, using, advertising and marketing of the product. The conventional ethics concept leads good and bad values in human perspective. Ethics was defined as an action that done based on the good moral principles where Akhlaq was being the main reference in doing of Islamic economics production. The foundation of Islamic ethics in advertisement is to follow the Sharia guideline that has been determined. The value of Islamic advertisement as follows: Shiddiq, (honest), Fathonah. (Clever). Amanah. (trusted) Tabligh. (delivered). Istiqomah. (consistent).